2005
DOI: 10.1111/j.1365-2036.2005.02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of gastro‐oesophageal reflux disease and the severity of obstructive sleep apnoea syndrome are not related in sleep disorders center patients

Abstract: SUMMARYBackground: Studies suggest obstructive sleep apnea syndrome (OSAS) frequently manifests in patients with gastroesophageal reflux disease (GERD) and that there may be a causal relationship. Aim: To determine the relationship between OSAS and symptoms of GERD. Methods: Consecutive patients referred to the Sleep Disorders Center (SDC) 18 years and older with polysomnographically defined OSAS were evaluated prospectively for GERD using a validated symptoms questionnaire. The GERD and OSAS relationship was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
4
31
1
Order By: Relevance
“…Second, we found no association between AHI or ArI and severity of nocturnal GER which would be expected if obstructive respiratory events were precipitating nocturnal GER events. These findings are consistent with some, but not all, previous studies [37,38]. The only studies that have reported a relationship between AHI and severity of GER have used symptoms [12] or endoscopic findings [39] to define GER severity, rather than pH monitoring, as was used in the present study.…”
Section: Mechanism Of Nocturnal Ger In Osasupporting
confidence: 94%
“…Second, we found no association between AHI or ArI and severity of nocturnal GER which would be expected if obstructive respiratory events were precipitating nocturnal GER events. These findings are consistent with some, but not all, previous studies [37,38]. The only studies that have reported a relationship between AHI and severity of GER have used symptoms [12] or endoscopic findings [39] to define GER severity, rather than pH monitoring, as was used in the present study.…”
Section: Mechanism Of Nocturnal Ger In Osasupporting
confidence: 94%
“…This is consistent with fi ndings of multiple studies in the past which showed lack of association between overall AHI and nGER severity. [16][17][18] The most recent study by Shepherd and Orr reported such fi nding by documenting the nGER by esophageal pH monitoring during polysomnography and suggested that obesity rather than AHI may have a greater role in the relationship between OSA and nGER. 17 This prompted us to perform further subgroup analyses, which revealed that the BMI of our patients with moderate-severe OSA (mean = 34.17 kg/m 2 ) was much higher than those with mild OSA (mean = 28.98 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Whilst most of the aforementioned studies did not control for sleep apnea, several recent studies have suggested that sleep apnea is not the underlying cause for GERD [51,52]. GERD and sleep apnea are two common disorders that share similar risk factors and thus may coexist in the same subject.…”
Section: Sleep Apneamentioning
confidence: 95%